Energy Performance Analysis of a Backpack Suspension System for Human Load Carriage - Kadhim, Jihad Hayder; Abdul Karim Hassan, Abdullah mohammed; Ahmed Khalil, Abdulhadi; Khamas, Harith Wathiq Talib; Alshemmery, Ahmed Saleem Munghr (American Journal of Botany and Bioengineering, 2025)
A backpack suspension system is designed and tested using a series of physical and numerical experiments for weight-bearing tasks in energy performance analysis. The system uses a modified shock-absorber with a bungee cord to establish a multi-stage interaction sequence to absorb energy at foot-strike, store energy in pre-compression, and release energy at take-off. A spring-mass-damper model is derived for energy performance analysis. The energy storage principle elaborated under this model is represented mathematically in functions that provide predictive features for optimal performance evaluation. The peak parking state energy is identified as the only unique outcome independent of the initial conditions. The energy basin construction shows that the model system has a basin of attraction encapsulating desirable parking conditions. Physical experiments demonstrate the energy performance of the suspension system on capturing and releasing energy during the human walking cycle and improve intuitive understanding of system performance. A backpack is a popular means to carry loads safely, quickly, and efficiently during human locomotion. A conventional backpack connects rigidly to the back of the user. The carried load translates according to the user's motion, inducing inertial forces that impair load carriage comfort and locomotion stability. An effective energy-storing backpack is under development that aims to reduce load inertia induced perturbation by capturing and releasing the energy created through load oscillation with a suspension mechanism. The suspension mechanism consists of a bungee cord connecting the load to the back frame. Experimental investigations are conducted to quantify the energy performance of the suspension system, capturing and storing energy from the foot-strike and releasing energy to take-off. A spring-mass-damper model is derived to analyze the energy performance of the suspension system. Mathematical representation of the energy storage principle under this model provides guidance for optimal energy performance.